Implicit evaluations and physiological threat responses in people with persistent low back pain and fear of bending - Caneiro, J.; O'Sullivan, Peter; Smith, Anne; Moseley, G.; Lipp, Ottmar (2017)
Background and aims: Pain and protective behaviour are dependent on implicit evaluations of danger to the body. However, current assessment of perceived danger relies on self-report, on information of which the person is aware and willing to disclose. To overcome this limitation, attempts have been made to investigate implicit evaluation of movement-related threatening images in people with persistent low back pain (PLBP) and pain-related fear. Lack of specificity of the sample and stimuli limited those explorations. This study investigated implicit evaluations and physiological responses to images of tasks commonly reported as threatening by people with PLBP: bending and lifting. We hypothesized that people who differ in self-reported fear of bending with a flexed lumbar spine (fear of bending) would also differ in implicit evaluations and physiological responses. Methods: This study used a convenience sample of 44 people (54% female) with PLBP, who differed in self-reported fear of bending. Participants completed a picture-viewing paradigm with pleasant, neutral and unpleasant images, and images of people bending and lifting with a flexed lumbar spine ('round-back') to assess physiological responses (eye-blink startle modulation, skin conductance). They also completed an implicit association test (IAT) and an affective priming task (APT). Both assessed implicit associations between (i) images of people bending/lifting with a flexed lumbar spine posture ('round-back' posture) or bending/lifting with a straight lumbar spine posture ('straight-back' posture), and (ii) perceived threat (safe vs. dangerous). Results: An implicit association between 'danger' and 'round-back' bending/lifting was evident in all participants (IAT (0.5, CI [0.3; 0.6]; p < . 0.001) and APT (24.2, CI [4.2; 44.3]; p = 0.019)), and unrelated to self-reported fear of bending (IAT (r = -0.24, 95% CI [-0.5, 0.04] , p = 0.117) and APT (r = -0.00, 95% CI [-0.3, 0.3], p = 0.985)). Levels of self-reported fear of bending were not associated with eye-blink startle (F(3, 114) = 0.7, p = 0.548) or skin conductance responses (F(3, 126) = 0.4, p = 0.780) to pictures of bending/lifting. Conclusions: Contrary to our expectation, self-reported fear of bending was not related to physiological startle response or implicit measures. People with PLBP as a group (irrespective of fear levels) showed an implicit association between images of a round-back bending/lifting posture and danger, but did not display elevated physiological responses to these images. These results provide insight to the understanding of the relationship between pain and fear of movement. Implications: The potential clinical implications of our findings are twofold. First, these results indicate that self-report measures do not always reflect implicit associations between particular movements and threat. Implicit association tasks may help overcome this limitation. Second, a lack of the predicted physiological and behavioural responses may reflect that the visualization of a threatening task by people in pain does not elicit the same physiological defensive responses measured in people with fear of specific objects. It may be necessary to expose the person to the actual movement to elicit threat-responses. Together, these results are consistent with current views of the role of 'fear' in the fear-avoidance model, in which a fear response may only be elicited when the threat is unavoidable.